Geochemistry of Eocene Bawang Member turbidites of the Belaga Formation, Borneo: Implications for provenance, palaeoweathering, and tectonic setting - Ahmed, N. (John Wiley and Sons Ltd, 2021)
The Belaga Formation of the Rajang Group or Rajang Fold and Thrust Belt (Late Cretaceous to Late Eocene) is mostly exposed in Sibu Zone along with some exposures in the Miri Zone of Central Sarawak. This entire turbiditic sequence was believed to have been deposited in a deep marine environment in a basin having an overall passive margin setting, that is, the Rajang Sea. However, the Eocene age-related stratigraphic record of this group (including Bawang Member) is much more complex, due to the complicated geological and tectonic settings which prevailed during their deposition. Here, we present field observations along with the application of various geochemical proxies and their constraints for the understanding of provenance, palaeo-weathering, and tectonic evolution of the area during the deposition of Bawang turbidites. Based on field observation, it has been found that this member consists of four main lithofacies, including massive sandstone facies (MSF), thick-bedded facies (TBF), heterolithic facies (HF), and mud facies (MF). Using geochemical data, chemical weathering indices (CIA and CIW) values and A-CN-K plot show that the source area for Bawang turbidites has undergone a moderate to an intense degree of chemical weathering and was influenced by the recycling effect. The slight depletion in sandstones and shales for Cr, Ni, and V values is consistent with the felsic dominated source region; however, La/Sc versus Co/Th and La/Th versus Hf plots show a mixed source (felsic and intermediate volcanic source) with some input of recycled sediments from the older sedimentary to metasedimentary rocks. Various geochemical ratios and discriminant diagrams verify that the Schwaner Mountains and its metamorphic group of rocks were the principal provenances for these sediments, along with some input from West Borneo. The results of the geochemical analysis also show that Bawang turbidite sediments were deposited in a basin associated with an initial active continental margin setting and the basin was shifting towards a passive setting (Late EoceneâOligocene). The volcanic input in Bawang Member during the Late Eocene also suggests the involvement of some subsequent possible arc setting around the âBawang subbasinâ. Â© 2020 John Wiley & Sons Ltd